1934
DOI: 10.1121/1.1915702
|View full text |Cite
|
Sign up to set email alerts
|

Extraneous Frequencies Generated in Air Carrying Intense Sound Waves

Abstract: The exact equation of the propagation of plane sound waves in air is not linear and consequently harmonics and combination tones are generated. The pressure of these extraneous frequencies in terms of the fundamental pressure, frequency, and distance from the source has been mathematically determined by Rayleigh, Lamb and others. These equations have been applied to an exponential horn. Measurements of the second harmonic and combination tones have been made at various points within a long tube, and in front o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1934
1934
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Most of the earlier work on nonlinear propagation was carried out using plane waves propagating in tubes [3][4][5][6], at sound levels in excess of 140 dB. The advantage in using plane waves is that the distortion occurs faster because the waves remain more intense over longer distances.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Most of the earlier work on nonlinear propagation was carried out using plane waves propagating in tubes [3][4][5][6], at sound levels in excess of 140 dB. The advantage in using plane waves is that the distortion occurs faster because the waves remain more intense over longer distances.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In general, this term becomes important when the dimensionless modulation frequency is on the order of, or larger than, the dimensionless attenuation coefficient a ¼ OðeÞ. In the context of plane waves, it was shown (Dontsov and Guzina, 2011a) that the modulationdriven contribution to the ARF can be used to explain the phenomenon of difference-frequency generation (Thuras et al, 1935) of the mean motion in lossless fluids where a ¼ 0. In the literature, the phenomena of difference-frequency generation and ARF were long thought to be unrelated owing to the common notion that the ARF vanishes in homogeneous lossless media (Ostorvsky et al, 2007), as indicated by the formula for g E z,dir in (94).…”
Section: Relationship Betweenĩ E Andĩmentioning
confidence: 95%
“…Thuras, Jenkins, and O'Neil (1935), Blackstock (1962b), Burns (1966a), Pernet and Payne (1969), and Cruikshank (1966). Each of the above researchers either ignored dispersion entirely or reported that its effects were slight.…”
Section: Discussionmentioning
confidence: 99%
“…The exception to this statement is the apparent necessity of including the effects of dispersion in our analysis. The necessity might be regarded as questionable, since Thuras, Jenkins, andO'Neil (1935), Geersten (1951), and Pernet and Payne (1969) A piece of evidence in support of validity of the value S has been reported by Shin (1963 Rudnick's theory but rather a working limit on the range of applicability of weak-shock theory. We have, nonetheless, compared both our threeterm result and numerical integration result (see Appendix E) with Rudnick's (1952) In a portion of the previously mentioned work by Pernet and Payne (1969), and in a later paper by the same authors [ Pernet and Payne (l971t>)], finite -amplitude noise propagation in tubes was considered.…”
Section: A)mentioning
confidence: 99%
See 1 more Smart Citation